Polycrystalline silicon thin films on glass obtained by nickel-induced crystallization of amorphous silicon - Schmidt, Javier Alejandro (2011)
In this work, we use the nickel-induced crystallization process to crystallize a-Si:H thin films at temperatures compatible with the utilization of glass substrates. Hydrogenated amorphous silicon films are deposited on planar float glass (Schott AF37) by plasma-enhanced chemical vapour deposition. The films, between 400 and 1400 nm thick, are grown intrinsic, slightly p-doped (p-) or with a combined structure of heavily p-doped / slightly p-doped (p+/p-) layers. On these films we sputter nickel with concentrations between 2.5×1014 and 3×1015 at./cm2 and then we anneal the samples in a standard nitrogenpurged tube furnace. The process evolves through the formation of the nickel silicide NiSi2, which has a lattice constant very similar to that of c-Si and acts as a nucleation centre. As a result of this thermal treatment we obtain thin polycrystalline films with a grain size over 100 μm. The high crystallinity of the samples is confirmed through optical and electron microscopy observations, Xrays diffraction and Raman spectroscopy.